2010
DOI: 10.1080/10496490903573114
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Banner Advertisements’ Attributes: A Content Analysis

Abstract: The web has received significant amount of attention from advertising and consumer researchers investigating the impact of banner advertisement on consumers' psychological and behavioral responses. However, no typology of banner advertisement has been identified yet, and the selection of banner advertisements as advertising stimuli has been carried out on the premise of personal judgment rather than scientific methodology. The identification of typology is important because different banner advertisement, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 43 publications
0
32
1
Order By: Relevance
“…Their findings also show most advertisements are small to medium in size, contrary to the findings of the wider literature which suggests bigger ads make for better advertising (Hussain et al, 2010). Source: Hussain et al (2010) Despite this literature being formed in the advertising field, their findings are important to this study as the current research conducted a similar study focused instead on professional sport sponsorship website presence.…”
Section: Existing Advertising Attributes Frameworkcontrasting
confidence: 58%
See 4 more Smart Citations
“…Their findings also show most advertisements are small to medium in size, contrary to the findings of the wider literature which suggests bigger ads make for better advertising (Hussain et al, 2010). Source: Hussain et al (2010) Despite this literature being formed in the advertising field, their findings are important to this study as the current research conducted a similar study focused instead on professional sport sponsorship website presence.…”
Section: Existing Advertising Attributes Frameworkcontrasting
confidence: 58%
“…Source: Hussain et al (2010) Despite this literature being formed in the advertising field, their findings are important to this study as the current research conducted a similar study focused instead on professional sport sponsorship website presence. Extending the work of Hussain et al (2010) by adopting the attributes they identified and utilising them in the field of sponsorship, this study incorporated work completed by Yu and Barnd (2003) who identified components associated with web advertising and sponsorship on professional sport team websites.…”
Section: Existing Advertising Attributes Frameworkmentioning
confidence: 87%
See 3 more Smart Citations